‘Capitulation of Ayacucho’ by Daniel Hernández: From event to canvas - Pineda Román, Iván (2024)
This article is a study that aims to reconstruct, from the limited available sources, the creation process of the painting Capitulation of Ayacucho by the national artist Daniel Hernández, within the context of the centennial commemorations of the Battle of Ayacucho in 1924. This information covers the depiction of the historical event and its protagonists, the background, motivations, and interpretations of the work, and the culmination of a series of celebrations surrounding the centenary.